2009
DOI: 10.1021/ja905056z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of 1,2,4-Triazoles via a Copper-Catalyzed Tandem Addition−Oxidative Cyclization

Abstract: A simple one-step synthesis of 1,2,4-triazole derivatives is provided by a copper-catalyzed oxidative coupling reaction under an atmosphere of air. The process should consist of sequential N-C and N-N bond-forming copper-catalyzed oxidative coupling reactions. Starting materials and the copper catalyst are readily available and inexpensive. A wide range of functional groups are tolerated to achieve chemical diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(121 citation statements)
references
References 21 publications
1
112
0
8
Order By: Relevance
“…Amidine hydrochlorides transformed into free amidines in the presence of base (Cs 2 CO 3 ), and intermolecular nucleophilic attack of amino in one amidine to carbon in another one leads to intermediate I. Treatment of I with copper in the presence of O 2 provides Cu(III) complex II (the similar metal complexes have been reported in the previous literature 15 ), and reductive elimination of II affords the target product (2) 14 leaving Cu(I) complex III. Further, reaction of III with I regenerates II, and the target product 2 16 continuously is provided in the catalytic cycle.…”
Section: The Synthesized N-[amino(m-tolyl)methylene]-4-methyl-mentioning
confidence: 74%
“…Amidine hydrochlorides transformed into free amidines in the presence of base (Cs 2 CO 3 ), and intermolecular nucleophilic attack of amino in one amidine to carbon in another one leads to intermediate I. Treatment of I with copper in the presence of O 2 provides Cu(III) complex II (the similar metal complexes have been reported in the previous literature 15 ), and reductive elimination of II affords the target product (2) 14 leaving Cu(I) complex III. Further, reaction of III with I regenerates II, and the target product 2 16 continuously is provided in the catalytic cycle.…”
Section: The Synthesized N-[amino(m-tolyl)methylene]-4-methyl-mentioning
confidence: 74%
“…Further studies of substituents effects demonstrated that the electron withdrawing groups like halogens and trifluoromethyl group on benzene ring gave the corresponding triazoles with good yields, while benzonitrile was substituted by methoxy group, the transformation efficiency was quite low to 55%. Acetonitrile could also be employed instead of benzonitrile to prepare triazoles in similar yield (52%) [176].…”
Section: Cyclizations Of Other Compoundsmentioning
confidence: 99%
“…Buchwald postulierte drei mçgliche Mechanismen für die oxidative Anellierung, die alle auf der Koordination des anhängenden Amidins zum Cu-Zentrum beruhen (Schema 31). Weg A beschreibt einen [91] Aus mechanistischer Sicht wird angenommen, dass die Reaktion über die Addition der 2-Aminogruppe an das Nitril verläuft und ein N-2-Pyridylamidin bildet, das dann eine kupferkatalysierte oxidative N-N-Kupplung eingeht. Die oxidative Cyclisierung eines vorab gebildeten Amidins verläuft ohne Zink problemlos, was andeutet, dass ZnI 2 lediglich an der Bildung des Amidins beteiligt ist.…”
Section: C-h-oxidationen Nach Art Metallorganischer Reaktionenunclassified